2020
DOI: 10.1007/s00441-020-03190-0
|View full text |Cite
|
Sign up to set email alerts
|

BXSB/MpJ-Yaa mouse model of systemic autoimmune disease shows increased apoptotic germ cells in stage XII of the seminiferous epithelial cycle

Abstract: In mammals, the reproductive system and autoimmunity regulate mutual functions. Importantly, systemic autoimmune diseases are thought to cause male infertility, but the underlying pathological mechanism remains unclear. In this study, the morpho-function of the testes in BXSB/MpJ-Yaa mice were analyzed as a representative mouse model for systemic autoimmune diseases to investigate the effect of excessive autoimmunity on spermatogenesis. At 12 and 24 weeks of age, BXSB/MpJ-Yaa mice showed splenomegaly and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, the presence of TLS in human kidney biopsies correlated with increased B cell hyperactivity and serum levels of CXCL13 (70). Subsequently, transcriptomic studies of LN kidneys in MRL/lpr and BXSB models showed increased cxcl13/cxcr5 along with upregulated expression signature associated with TLS formation (63), suggesting a role of CXCL13/CXCR5 in TLS formation in LN. In animal studies, BAFF, TLR7 signaling, and Fli-1 have also been suggested to play a role in TLS formation (54, 65,71).…”
Section: Potential Mechanisms Underlying Tls Formation In Lnmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the presence of TLS in human kidney biopsies correlated with increased B cell hyperactivity and serum levels of CXCL13 (70). Subsequently, transcriptomic studies of LN kidneys in MRL/lpr and BXSB models showed increased cxcl13/cxcr5 along with upregulated expression signature associated with TLS formation (63), suggesting a role of CXCL13/CXCR5 in TLS formation in LN. In animal studies, BAFF, TLR7 signaling, and Fli-1 have also been suggested to play a role in TLS formation (54, 65,71).…”
Section: Potential Mechanisms Underlying Tls Formation In Lnmentioning
confidence: 99%
“…These animals had a higher ex vivo FDG accumulation in the kidney of anti-dsDNA antibody positive group compared to antibody-negative mice, which is consistent with the presence of large population of metabolic active or activated immune cells (35). Thus, TLS may contribute to LN in multiple ways (Table 5), such as by being a local source of activated immune cells (35), local IFN-I production (61), maintaining systemic autoantibody production (66, 78), site for intermolecular epitope spreading (80, 81) to local autoantigens such as to locally overexpressed vimentin (79), and facilitating tubulointerstitial inflammation (63,68).…”
Section: Possible Contributions Of Tls To Lnmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these models, the BXSB/MpJ-Yaa in which there is a Y chromosome-linked autoimmune acceleration gene accelerates the systemic autoimmune disease in males (Henry & Mohan, 2005). Recently, our team showed some histopathological abnormalities in the testis of the BXSB/MpJ-Yaa mice including an increased number of both residual bodies and apoptotic germ cells in stage XII, and decreased numbers of Sertoli cells, and concluded that these testicular lesions could play a role in the pathogenesis of reproductive dysfunction in this autoimmune disease mouse model (Otani et al, 2020). The MRL/MpJ mice are the control strain of MRL/MpJ-Fas lpr (MRL/lpr) mice and show mild autoimmune disease in older ages (Heydemann, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…The knowledge of how systemic autoimmune disease histologically alters the testis is limited (Otani et al, 2020). However, the morphological testicular alterations in the testes of MRL/lpr mice have not studied yet.…”
Section: Introductionmentioning
confidence: 99%